Pelatihan Dan Pemberdayaan Kader Dan Pendamping Keluarga Tentang Faktor Risiko Penyakit Tidak Menular (PTM) Di Posbindu Berkah Barokah Desa Limamar Wilayah Kerja Puskesmas Astambul - sajidah, ainun; Mariana , Evi Risa; Hammad, Hammad; Rahmah, Adila Alfina; Nazmi, Syaima; Kaila, Wafa (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Based on the NCD data in the working area of Puskesmas Astambul, there is a tendency of increase from 2017 to 2020. In 2017, there were 1,780 cases of hypertension and 109 cases of diabetes mellitus (DM). Although the cases of hypertension and diabetes mellitus decreased in 2021, they remained high with 757 and 241 cases respectively. However, cases of hypertension increased again in 2022 to 1,480 cases. From this data, it can be seen that the most common NCDs in the working area of Puskesmas Astambul are hypertension and diabetes mellitus. The goal of the community service is to enhance knowledge and provide services to target partners regarding the prevention and control of non-communicable diseases (Hypertension and Diabetes Mellitus) through "Posbindu PTM: Training and Empowerment of Cadres and Family Companions on Risk Factors for Non-Communicable Diseases (NCDs)" at Posbindu Berkah Barokah in Limamar Village, Puskesmas Astambul working area. Activities include health education by equipping the community with simple screenings related to hypertension and diabetes mellitus, such as blood pressure measurement and blood sugar tests, and creating a specific work program at Posbindu Berkah Barokah in Limamar Village related to NCDs hypertension and diabetes mellitus. Health education is conducted twice, accompanied by pre-tests and post-tests. The results of the community service activities show an increase in knowledge and skills of patients and families regarding hypertension. Individual knowledge influences awareness of hypertension prevention behaviors. Additionally, there is an increase in knowledge and skills of patients and families regarding diabetes mellitus